2022
DOI: 10.3390/a15120450
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Exact–Local Search Approach for One-Machine Scheduling with Time-Dependent Capacity

Abstract: Machine scheduling is a hard combinatorial problem having many manifestations in real life. Due to the schedule followed, the possibility of installations of machines operating sub-optimally is high. In this work, we examine the problem of a single machine with time-dependent capacity that performs jobs of deterministic durations, while for each job, its due time is known in advance. The objective is to minimize the aggregated tardiness in all tasks. The problem was motivated by the need to schedule charging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Other recently related studies can be found in Zhang et al [12], Masadeh et al [13], Zhang et al [14], Kim and Kim [15], Valouxis et al [16], and Wang et al [17] among many others.…”
Section: Notation Terminology P Jmentioning
confidence: 91%
“…Other recently related studies can be found in Zhang et al [12], Masadeh et al [13], Zhang et al [14], Kim and Kim [15], Valouxis et al [16], and Wang et al [17] among many others.…”
Section: Notation Terminology P Jmentioning
confidence: 91%
“…In the paper [11], single machine scheduling problems with time-dependent capacity and the objective to minimize the total aggregated tardiness are considered. The authors formulate linear programming and constraint programming models.…”
Section: Special Issuementioning
confidence: 99%
“…Examples of problems belonging to the first case are the problem of scheduling independent tasks to heterogeneous multiprocessors [26] and the machine reassignment problem [27]. On the other hand, an example of the second case is the one-machine scheduling problem [28] that is an abstraction of a real-world scheduling problem that is aimed at achieving efficient charging of electrical vehicles. Another paper that proposes an approximation approach for the one-machine problem, this time including release and delivery times for the jobs, is [29].…”
Section: Related Workmentioning
confidence: 99%